Dracula - Stoker, Bram; Humphries, Tudor (New York DK Pub., 1997)
After discovering the double identity of the wealthy Transylvanian nobleman, Count Dracula, a small group of people vow to rid the world of the evil vampire. Illustrated notes throughout the text explain the historical background of the story.
70865
Keywords: Vampires -- Fiction; Horror stories